Hydrologic Performance Analysis of a Coastal Reservoir for Urban Flood Management - Emir Hansen Pasaribu, David; Sisinggih, Dian (Fakultas Teknik, Universitas Brawijaya, 2026)
Jakarta continues to experience severe flooding due to extreme rainfall and limitations in existing flood‑control infrastructure. As part of the city’s integrated coastal defense system, the East Side Coastal Reservoir (ESCR) is intended to function as the final component after upstream dams, levees, retarding basins, and estuary water gates. Its effectiveness, however, depends on whether its reservoir storage capacity can accommodate extreme flood volumes generated within the catchment area. This study assesses the hydrologic performance of the ESCR by estimating flood volumes for return periods of 2, 5, 10, 50, 100, 200, and 1000 years. The methodology integrates spatial analysis using Google Earth Pro and QGIS to derive catchment characteristics, including DEM‑based topography and soil type data, followed by hydrologic modeling using HEC‑HMS. Flood volumes were computed using the water‑loss method and compared against the reservoir storage capacity. Results show that the ESCR provides 145 million m³ of storage, whereas the 1000‑year return‑period flood generates 297 million m³ of runoff. Thus, the reservoir can accommodate only 48.87% of the extreme event, indicating limited effectiveness for large‑magnitude floods. These findings offer important insight for future coastal reservoir planning and design in Jakarta.